Nanometrology of Biomass for Bioenergy: The Role of Atomic Force Microscopy and Spectroscopy in Plant Cell Characterization - Charrier, Anne M.; Lereu, Aude L.; Farahi, Rubye H.; Davison, Brian H.; Passian, Ali (Frontiers in Energy Research, 2018)
Ethanol production using extracted cellulose from plant cell walls (PCW) is a very promising 4 approach to biofuel production. However, efficient throughput has been hindered by the pheno5 menon of recalcitrance, leading to high costs for the lignocellulosic conversion. To overcome 6 recalcitrance, it is necessary to understand the chemical and structural properties of the plant 7 biological materials, which have evolved to generate the strong and cohesive features observed 8 in plants. Therefore, tools and methods that allow the investigation of how the different molecular 9 components of PCW are organized and distributed and how this impacts the mechanical proper10 ties of the plants are needed but challenging due to the molecular and morphological complexity 11 of PCW. Atomic force microscopy (AFM), capitalizing on the interfacial nanomechanical forces, 12 encompasses a suite of measurement modalities for nondestructive material characterization. 13 Here, we present a review focused on the utilization of AFM for imaging and determination of 14 physical properties of plant-based specimens. The presented review encompasses the AFM 15 derived techniques for topography imaging (AM-AFM), mechanical properties (QFM), and sur16 face/subsurface (MSAFM, HPFM) chemical composition imaging. In particular, the motivation and 17 utility of force microscopy of plant cell walls from the early fundamental investigations to achieve 18 a better understanding of the cell wall architecture, to the recent studies for the sake of advancing 19 the biofuel research are discussed. An example of delignification protocol is described and the 20 changes in morphology, chemical composition and mechanical properties and their correlation at 21 the nanometer scale along the process are illustrated.